Optimization of Cognitive Diagnostic Assessment with the Project-Based Learning Model on Understanding Fluid Concepts in Middle School - Viclara, Dinicen (JURNAL PEMBELAJARAN FISIKA, 2025)
Based on research over the past three years, the average for the implementation of diagnostic assessments shows that they still feel unfamiliar with its use. Then, the implementation of cognitive diagnostic assessments on fluid material often only reveals the inability to memorize rather than conceptual understanding. Teachers have received sufficient training regarding its implementation, but there are still obstacles in students' understanding of science concepts related to fluid material. The objective of this research focuses on discussing the optimization of cognitive diagnostic assessment with the PjBL learning model. This study uses a quasi-experimental approach with a pretest-posttest control group design. The subjects of the study are eighth-grade students at a junior high school implementing the Merdeka Curriculum. The class was divided into two groups, namely the experimental class that applied the Project-Based Learning (PjBL) model with the optimization of cognitive diagnostic assessment, and the control class that used conventional teaching methods. The results of this study show a significant difference in pre-test and post-test scores (p<0.001). The average gain score of 24.34 indicates the effectiveness of PJBL learning by optimizing cognitive diagnostic assessment. Although teachers have received adequate training on cognitive diagnostic assessments, there are still obstacles in students' understanding of science concepts, especially in fluid materials. Therefore, the PjBL approach with structured diagnostic assessment can be a solution to overcome these obstacles. This study also highlights the importance of remedial support for students who have not yet achieved competence in understanding fluid concepts. By aligning learning based on the average competency of students, teachers can provide more targeted interventions. In general, the combination of the PjBL model and cognitive diagnostic assessment can be an effective learning strategy in the Merdeka Curriculum.